FOREIGN DIRECT INVESTMENTS IN THE ECONOMY OF UKRAINE: STATUS, TRENDS AND PROSPECTS ATTRACTION - Диха, Марія Василівна; Диха, Валерій Валерійович; Зима, Віталій Миколайович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article analyzes the volume of inflows of foreign direct investment into the economy of Ukraine. It is noted that despite Ukraine's existing potential, the volume of attracted foreign direct investment in the national economy during the years of independence was low. Such volumes were determined by the unfavorable investment and business climate, which was characterized by macroeconomic and political and legal instability, risks, characteristics of the business environment in Ukraine, etc. In the difficult conditions of Russian aggression and military operations in Donbas since 2014, Ukraine has maintained its economic situation at a relatively stable level; during 2015-2019, the volume of attracted direct investments in Ukraine increased, but did not reach the level of investments made in 2013. The consequences of the spread of COVID-19 led to a decrease in the volume of investments attracted to Ukraine in 2020, but in 2021, the positive dynamics of attracting investments to Ukraine resumed. The volume of inflows of foreign direct investment into Ukraine was analyzed by industry and investor countries; the practice of tax optimization was noted, because the largest share of direct foreign investments came from Cyprus and other offshores, which to a large extent are finances of Ukrainian "origin"; investments do not determine the innovative nature of the development of industries. It was noted that there was a high level of presence of Russian capital in certain branches of the national economy, which caused the total control of the development of these branches in Ukraine; by the end of 2021, the presence of Russian capital in the economy of Ukraine decreased to 1.81% of the total volume of foreign direct investments. The importance of diversifying the sources of attracting direct foreign investment to Ukraine, as well as the importance of attracting investments in the form of the latest technologies, environmentally safe productions, is substantiated. The prospects of large-scale investments in the economy of post-war Ukraine are outlined. The need to solve problems (to overcome corruption, to ensure equal and transparent conditions for doing business, to ensure trust in state authorities and the judicial system, etc.) that hinder the attraction of investments is substantiated.